Synthesis and bioactivity of teasterone and typhasterol analogs - Ramírez, J.A. (2000)
Four brassinosteroids analogs of homoteasterone and homotyphasterol bearing 5α-OH and 5α-F groups have been synthesized and their bioactivities evaluated.